XOR-Based Hierarchical Secret Sharing Scheme - Shima, Koji; Doi, Hiroshi (Advances in Information and Computer Security, 2018)
Hierarchical secret sharing schemes are known for how they share a secret among a group of participants partitioned into levels. In this study, we apply the general concept of hierarchy to Kurihara et al.’s XOR-based secret sharing scheme and propose a hierarchical secret sharing scheme applicable at any level. In our scheme, a minimal number of higher-level participants are required for recovery of the secret. Such hierarchical schemes applicable at any level over finite fields have been proposed, but no XOR-based hierarchical schemes applicable at any level have been reported. We realize the first such scheme. Moreover, considering practical use, we present an evaluation of our software implementation.